2009
DOI: 10.2474/trol.4.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbonizing Temperature on Friction and Wear Properties of Hard Porous Carbon Materials Made from Rice Husk

Abstract: The new hard porous carbon material called the RH (rice husk) ceramics has been developed by carbonizing rice husk as the main raw material. In order to clarify the friction and wear properties of RH ceramics, a study of the effect of carbonization temperature on the mechanical and tribological properties of RH ceramics was undertaken. RH ceramics samples carbonized at 900, 1400, and 1500 °C were prepared for this study. The RH ceramics samples were inspected using X-ray diffraction, EDX and scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…,米糠 (7)(8)(9)(10)(11)(12) ,籾殻 (13)(14)(15)(16)(17)(18) などを原料とした植物 由来炭素材料の研究が進められている。炭素材料は自己潤滑 性,耐薬品性,耐熱性に優れており,金属材料を使用できない 薬液中や,潤滑剤を使用できない高温乾燥の環境下での摺動材 料として用いられる。堀切川らは,フェノール樹脂をバインダ に使用して,米糠と籾殻に由来する RB セラミックスと RH セ ラミックスを製造した。900-1000℃で焼成した RB セラミッ クスとRH セラミックスは,摩擦係数0.07-0.17,比摩耗量1.0×…”
Section: はじめにunclassified
“…,米糠 (7)(8)(9)(10)(11)(12) ,籾殻 (13)(14)(15)(16)(17)(18) などを原料とした植物 由来炭素材料の研究が進められている。炭素材料は自己潤滑 性,耐薬品性,耐熱性に優れており,金属材料を使用できない 薬液中や,潤滑剤を使用できない高温乾燥の環境下での摺動材 料として用いられる。堀切川らは,フェノール樹脂をバインダ に使用して,米糠と籾殻に由来する RB セラミックスと RH セ ラミックスを製造した。900-1000℃で焼成した RB セラミッ クスとRH セラミックスは,摩擦係数0.07-0.17,比摩耗量1.0×…”
Section: はじめにunclassified
“…However, the same was not detected for A 2 lO 3 , hence the high friction coefficient (0.14-0.23). The study also investigated the effect of carbonization temperature (900 °C, 1,400 °C, and 1,500 °C) on the tribological performance of the RHC and found 900 °C as the best carbonization temperature [9]. However, research on the effects of load and velocity on the tribological behaviors of RHC adobes (RHAs) remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors also investigated the effect of the variation of carbonization temperature (900, 1,400, and 1,500 °C) on the tribological performance of RHC particles. They found that 900 °C was the optimum carbonization temperature [7]. Shibata et al [8] also investigated the tribological performance of disk-shaped RHC materials sliding against stainless steel, alumina, silicon carbide, and silicon nitride under dry conditions.…”
Section: Introductionmentioning
confidence: 99%